Human growth hormone use in poor ovarian response - caution and opportunities - Robert J. Norman; Roger J. Hart (SAGE Publishing, 2021)
Human growth hormone has found favour as a co-gonadotrophin in assisted reproduction particularly in the circumstances of a poor response to stimulation. Its use has been based on animal studies suggesting insulin-like growth factor-1 enhances granulosa and cumulus cell function and possibly oocyte quality. While there is limited ovarian cellular information in women, the use of human growth hormone is alleged to improve egg numbers, embryo quality, clinical pregnancies and live birth in women with a poor ovarian response. A number of cohort studies have claimed these benefits compared with prior nil treatment, but there are a limited number of quality randomised controlled studies. The few good randomised trials indicate an enhanced ovarian response in terms of oestradiol secretion and oocyte maturity with controversial improvement in ongoing pregnancy and live birth. Given the cost of the medication, the lack of convincing data on enhanced clinical outcomes and the theoretical possibility of side effects, we propose it is still too early to determine human growth hormone's true cost-benefit for widespread use. However, a number of emerging randomised trials may tilt the equation to a positive outlook in the future. Meanwhile, the hormone should only be used after full informed consent from the patient as to its effectiveness and efficacy.